Mentor-shape: exploring the mentoring relationships of Black women in doctoral programs. Issue 1 (1st January 2018) - Rasheem, S.; Alleman, Ali-Sha; Mushonga, Dawnsha; Anderson, Darlene; Ofahengaue Vakalahi, Halaevalu F.
Abstract: Using a Black Feminist Thought framework, this phenomenological study focused on lived experiences with mentoring relationships among 38 Black women in doctoral programs in multiple disciplines across universities in the United States. Although emerging studies on Black women in academia acknowledge the significance of mentorship and the reality of discrimination at the intersection of race and gender, the literature lacks empirical support pertaining to the formation and outcomes of mentoring relationships, specifically for Black women in doctoral education. Findings from this study suggested four central themes in the mentoring relationships among Black women in doctoral programs: (a) organic evolvement, (b) shared identity/mutual interest, (c) personal transformation and (d) increase in access and opportunity. Implications for future research, policy, practice and education across disciplines are offered.